FINANCIAL LITERACY AS THE MODERATOR OF PAYMENT GATEWAY TRANSACTION AND FINANCIAL INCLUCION ON MICRO ENTERPRISES FINANCIAL PERFORMANCE AT BOJA KENDAL - Sutrisno, Sutrisno; Setiawati, Ira; Pratama, Hendri Septawidya (Universitas PGRI Semarang, 2023)
The purpose of this study is to analyze the effect of payment gateway transactions and financial inclusion on financial performance with financial literacy as a variable that can strengthen the relationship between variables. This study used a quantitative research method with a sample of 130 micro entrepreneurs in Boja District. Testing the data obtained in this study using the Partial Least Square - Structural Equation Modeling (PLS-SEM) technique with the help of SmartPLS 3.2.9 software. The results of this study state that payment gateway transactions affect financial performance with a P-Value 0.000. Financial inclusion has no effect on financial performance with a P-Value 0.163. The results of this study also state that financial literacy strengthens the influence of the relationship between payment gateway transactions on financial performance with a P-Value 0.001, but financial literacy actually weakens the effect of the relationship between financial inclusion on financial performance with a P-Value 0.220.